Analysis Of Production And Prices Of Sky Fish And Mackarel Tuna At The Ocean Fishery Port Lampulo Aceh - Hamdani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research aims to determine production patterns, production quantities and factors that influence the prices of tuna and flying fish at auctions at PPS Kutaraja Lampulo Banda Aceh, namely (1) descriptive statistics and (2) simple linear regression parametric statistics. The results of the research show that the production patterns of tuna and flying fish fluctuate, due to the influence of the fishing season. Using a simple linear regression research method. The results of the regression analysis show that there are two variables that influence the price of tuna, namely the amount of production with a significant degree. Meanwhile, the price of flying fish is not significantly influenced by production factors.